Studies on Corynespora Cassiicola (Berk. & Curt.) Wei on Rubber - Dung, Phan Thanh (1995)
Corynespora cassiicola (Berk. & Curt.) Wei from infected rubber leaves in Sungai Buloh (two isolates) and Serdang (two isolates) were cultured on Potato Dextrose Agar (PDA). All four isolates exhibited variability in colony colour and growth rates on artificial media (PDA, PSA, RLEA and WA). The optimum temperature for growth on PDA was 28°C. Significant increase in sporulation was recorded on Potato Sucrose Agar (PSA) when exposed to uv light for 2 h daily for three days. Exposure to nuv light also increased sporulation significantly but maximum sporulation occurred only with 4 h daily treatment. Conidial size, hilum width and septal number of isolates cultured on , PSA were variable and were not affected by uv light treatment. The size and shape of conidia on PSA differed from those on naturally infected rubber leaves. On rubber leaves, the average conidial and hilum width were longer, and the average septal number was higher. Conidia were long, slender and stick-like in culture, but were curved, with a broader based on rubber leaves. Maximulll sporulation was achieved when cultures on PSA were scraped once, and maintained for three days under continuous fluorescent light with 2 h exposure to uv light daily. By this method, variation of uv light exposure of between 15 mi n to 4 h daily was found to have no negative effect on conidial germination and germ tube growth. PSA was the best medium for sporulation compared to PDA and RLEA. The addition of yeast extract in these media did not improve sporulation.